Primary adrenal insufficiency presenting with neuropsychiatric illness - Yadav, Lokesh; Khosla, Pooja; Taneja, Vinus; Dessai, Rishikesh (International Journal of Research in Medical Sciences, 2023)
Adrenal insufficiency is characterized by decreased production of glucocorticoids from adrenal cortex, either due to a primary adrenal or a secondary pituitary etiology. Neuropsychiatric symptoms and signs could be the first presenting symptoms or the only presentation of adrenal insufficiency and are relatively less explored in patients with adrenal insufficiency and less understood. Patients with chronic psychiatric symptoms, namely depression and anxiety should be evaluated for association with adrenal insufficiency.